Elucidation of Hosts, Native Distribution, and Habitat of the Coffee Berry Borer (Hypothenemus hampei) Using Herbaria and Other Museum Collections - Vega, Fernando E.; Smith, Lucy T.; Davies, Nina M. J.; Moat, Justin; Góral, Tomasz; O’Sullivan, Robert; Davis, Aaron P. (Frontiers in Plant Science, 2019)
The coffee berry borer (Hypothenemus hampei) is the most damaging insect pest of global coffee production. Despite its importance, our knowledge on the insect’s natural habitat, range, and wild host species remains poorly known. Using archival sources (mainly herbaria but also other museum collections), we surveyed 18,667 predominantly wild-collected herbarium specimens mostly from Africa, Madagascar and Asia, for coffee berry borer occurrence. A total of 72 incidence were confirmed for presence of the coffee berry borer, with identifications assisted by micro-CT for SEM. Of the 72 positive infestations all were from tropical African coffee (Coffea) species, of which 32 were from wild (non-cultivated) plants. Of the 32 wild occurrences, 30 were found in C. canephora (robusta coffee), one in C. liberica (liberica coffee), and one in C. arabica (Arabica coffee). Our herbarium survey confirms literature and anecdotal reports that the coffee berry borer is indigenous to tropical Africa, and that coffee species, and particularly robusta coffee, are important hosts. We identify the wetter type of Guineo-Congolian forest as either the preferred or exclusive native habitat of the coffee berry borer. Other that coffee, we find no evidence of other naturally occurring hosts. Characters of infestation (e.g., hole position on coffee fruits) infers a certain degree of specificity between coffee and the coffee host.